Development Mathematics Teaching Materials Based on Sway 365 for Student Class IV School Basics - Practicality - Yola Monica Efriani; Alwen Bentri (Budapest International Research and Critics University, 2022)
This research is a development research. The purpose of this study was to reveal the level of practicality of Microsoft Sway 365 -based mathematics teaching materials for fourth grade elementary school students. The research instrument used was a practical questionnaire sheet for student responses and teacher responses. The research subjects were fourth grade students of SD Plus Marhamah. The results of the practicality test, namely the student response obtained a score of 4.23 in the very good category and the results of the teacher's response obtained a score of 4.4 in the good category. So it can be decided that Microsoft Sway 365 -based mathematics teaching materials are practical to use for fourth grade elementary school students.